Hybrid renewable/conventional energy system for rural community - Foo, Eddy Yi Shyh. (2009)
The Final Year Project (FYP) is part of the curriculum for all engineering students in Nanyang Technological University (NTU). The objective of this report is to document research findings and summarize the learning experiences of the student over a period of two academic semesters (AY 2008 / 2009). The report is categorized into five main sections: Project Overview, Literature review, Simulation Studies, Summary, Recommendations and Conclusion. An overall project description is provided under Project Overview to allow readers to have an overall impression of the project. Next, Literature Review will provide some theories which will be needed for sample computation and analysis. Simulation Studies will document simulation results and analysis using a software program called HOMER and will also include system analysis and evaluating reliability of optimized system design. Next, recommendations will provide future challenges in areas where the project can further develop. Lastly, Conclusion will summarize the research and analysis done by the student during the FYP period.